An analysis of pivotal factors in the implementation of occupational health and safety management systems in micro, small and medium enterprises (MSMEs): Literature review - Mila Tejamaya; Wishnu Puspoprodjo; Heru Susetyo; Robiana Modjo (Elsevier, 2021)
Objective: In its aim to develop a model of an occupational safety and health management system (OSHMS) for MSMEs in Indonesia, this study seeks to explore crucial factors in relation to the implementation of such a system in MSMEs by conducting a review of previous studies on the topic. Methods: This systematic review is an exploratory study from several online databases our using a combination of two keywords that refer to the population and exposure variables in the PROSPERO Approach by using the "AND" strategy. Each literature goes through selection based on PRISMA flow chart. A Critical Appraisal Skill Programme (CASP) checklist for risk of bias assessment was used for the evidence quality appraisal. Result: From 37 papers, books, online books and local articles were selected, we identified pivotal factors in the implementation of OHSMS in MSMEs which can be classified into downstream factors (OSH training, commitment, risk management, and communication), middle stream factors (support from the third party), and upstream factors (the role of government). Conclusion: Various pivotal factors in promoting OSH implementation at MSMEs can be seen as role of MSMEs actors (employer and employee); third party and government.